Book Review of Research and Publication Ethics, written by Santosh Kumar Yadav, Switzerland: Springer Cham, 2023, 255 pp, ISBN 9783031269714, Ebook: $93.08 USD - Vernando Yanry Lameky; Heru Santoso Wahito Nugroho (Health Dynamics, 2024)
Research and Publication Ethics includes principles that guide researchers in conducting and disseminating research ethically. Emphasize integrity, honesty, openness, and respect for subjects' rights, preventing conflicts of interest. Adhering to these principles is critical to maintaining trust and credibility in research. Addressing violations such as plagiarism ensures reliability and credibility. Technology helps detect plagiarism, while open research practices encourage transparency and validation. Upholding a code of ethics and participating in ethical forums further strengthens ethical behaviour. Understanding digital data ethics is very important. This book review reflects the importance of ethical practices in research and publication integrity.